Policy Implementation Regarding The Duties And Functions Of Village Head In Organizing Village Administration In Peana Village, Pipikoro District, Sigi Regency, Central Sulawesi - Syahruddin Hattab; Daswati Daswati; Mustainah Mustainah (Indonesian Association for Public Administration (IAPA), 2018)
The Village Government is an institution that functions to organize village administration towards good governance. This study aims to analyze the implementation of the policy on the duties and functions of the village head in administering the administration of the Peana village, Pipikoro district, Sigi regency, Central Sulawesi Province, with reference to the aspects of communication, resources, disposition and bureaucratic structure. This qualitative research is carried out in Peana Village which is geographically isolated with limited infrastructure. Data were obtained from informants which are village officials and the community. Data are collected through observation to observe the behaviour naturally, original and spontaneous within a certain period of time to obtain careful, in-depth and detailed data. The data also obtained from documents originating from books, government regulations in the Peana Village Office as well as interview with the village secretary, village staffs and community members. The results showed that socialization about the content, purpose, direction and target group had not been implemented. Human resources, infrastructure and budget resources were inadequate. Village government disposition in responding to policies is not maximized. Bureaucratic structure in policy implementation, was not guided by standard operating procedure (SOP). The conclusion is that the task and function of the village head in the village administration is not optimally implemented, because the village head has not optimally responded regarding the administration of village administration. For this reason, the researcher recommends that the village head should be more active in responding to his duties and functions with the provided assistance by the academics, so that preparation and planning can be carried out effectively and efficiently.